On the Need of a Comprehensive Risk Assessment of the Implementation for Major Infrastructure Projects in Kaliningrad (Vistula) Lagoon - GUMENUK, Ivan S.; KILESOV, Alexander V.; GRITSENKO, Vladimir A.; CHERNISHKOV, Pavel P. (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505//jemt.v7.4(16).09, 2017)
Kaliningrad/Vistula lagoon is divided by state border into two approximately equal parts that belong to the Republic of Poland and the Russian Federation. In the context of cross-border nature of the gulf, the implementation of large-scale projects – projects for the construction of a deepwater port in the Russian part of the gulf or the navigable channel on the Polish part of the spit – acquire the level of international cross-border projects that require coordination and approval at the international level, as the effects (primarily geo-ecological) from the implementation of such projects affect both sides of the unified nature system of the bay. As part of this work, the authors analyze the complex and in many ways contradictory situation around the Polish project to build a navigable channel through the Polish part of the Baltic/Vistula spit. The main conclusion that the authors make – projects of this magnitude require the joint interstate approval, including the consent of all the inhabitants of the coastal areas of the Kaliningrad / Vistula bay.